Circulating inflammatory cytokines and sarcopenia-related traits: a mendelian randomization analysis - Sun, Aochuan; Liu, Saiya; Yin, Fen; Li, Zhuangzhuang; Liu, Zhengtang (Frontiers in Medicine, 2024)
Objective To explore the causal relationships between 91 circulating inflammatory cytokines and sarcopenia-related traits (low hand grip strength, appendicular lean mass, and usual walking pace) by Mendelian randomized analysis. Methods Independent genetic variations of inflammatory cytokines and sarcopenia-related traits were selected as instrumental variables from publicly available genome-wide association studies (GWAS). The MR analysis was primarily conducted using the inverse variance-weighted (IVW) method. Sensitivity analyses included Steiger filtering and MR PRESSO, with additional assessments for heterogeneity and pleiotropy. Results The IVW method indicated a causal relationship between Vascular Endothelial Growth Factor A (VEGF-A) and low hand grip strength (OR = 1.05654, 95% CI: 1.02453 to 1.08956, P = 0.00046). Additionally, Tumor Necrosis Factor-beta (TNF-β) was found to have a causal relationship with appendicular lean mass (ALM) (β = 0.04255, 95% CI: 0.02838 to 0.05672, P = 3.96E-09). There was no evidence suggesting a significant causal relationship between inflammatory cytokines and usual walking pace. Conclusion Our research substantiated the causal association between inflammatory cytokines, such as VEGF-A and TNF-β, and sarcopenia. This finding may provide new avenues for future clinical treatments.